MODIFIKASI PERATURAN PERMAINAN TRADISIONAL PRESEAN TINGKAT SEKOLAH DASAR DI SD ISLAM NW TANAH ABROR - Aminullah, Aminullah -; Afrian, Herman -; Suryansah, Suryansah - (Universitas Hamzanwadi, 2018)
This research aim to yield modification regulation of traditional game of peresean of elementary school storey level in SD Islam NW Tanah Abror. this Type Research represent research of development yielding product use (development and research education (R and D) with the following step: (1) Product development. (2) Gathering of information. (3) Product desain (model draft). (4) Expert validasi and revise. (5) Small scale field test-drive and revise. (6) Big scale field test-drive and revise. (7) Making of final product, revise small scale test-drive at 10 Elementary student of SD Islam NW Tanah Abror . (8) Big scale product test-drive at 20 SD Islam student of NW Tanah Abror and (9) Reviseing product is: Interview and kuesioner. Technique analyse data that is descriptive analysis qualitative and is quantitative. Result indicate that traditional game modification of peresean for elementary school in Elementary School Islam NW Tanah Abror effective and good direspon. This matter is proved with result of expert analysis equal to 72% with good katagori, beside itupula percentage of student counted 83,02% with good katagori. So that can be concluded that modification regulation of traditional game of peresean of elementary school storey level in SD Islam NW Tanah Abror can be used effectively.